The Effect Of Coix lacryma-jobi L Local Food Substitution On Acceptance Of Brearfruit Fettuccine - Nur Fitri Masyitha; Mahdiyah Mahdiyah; Efrina Efrina (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
The purpose of this study was to study the effect of hanjeli flour substitution on the manufacture of breadfruit fettuccine on consumer acceptance which was tested by Friedman Tests. It also conducted a test time of cooking and water absorption index. This research is using experimental method. The sample in this study was fresh breadfruit fettuccine with 60%, 70%, and 80% hanjeli flour substitution which was then tested on 30 untrained panelists. The test results showed that the substitution of hanjeli flour in the manufacture of breadfruit fettuccine only affected the aroma aspect. Based on the results of the Tukey test on the aroma aspect, the formula most favored by consumers and recommended is the substitution of 60% hanjeli flour. In the cooking time and water absorption index tests, it was found that there was no significant effect. However, cooking time affects the water absorption index. This is directly proportional to the water absorption index and the change in dimensions, where the longer the cooking time, the more the pasta will absorb water. Fettuccine breadfruit substituted with hanjeli flour with a percentage of 80% is the sample with the best water absorption index value in the al dente cooking process.